Fault-tolerant control for a class of quantised networked control of nonlinear systems with unknown time-varying sensor faults. Issue 3 (3rd March 2020) - Tahoun, A. H.
ABSTRACT: In this paper, fault-tolerant control problems in quantised networked control of nonlinear systems (NCSs) with sensor uncertainties are considered. The measured output equation of the given NCS system has unknown external time-varying uncertainties that may be unbounded in addition to the effects of network-induced constraints; network-induced delays, network-induced data packet losses and network quantisation errors. A simultaneous observer-controller is constructed to stabilise the overall NCS. A flexible-joint robot link example is simulated to illustrate the significant improvement on system tracking performance.